Kinetic and biochar characteristics of lignocellulosic and protein-based industrial wastes during co-pyrolysis - Kocer, Anil Tevfik; Erarslan, Azime; Yurtseven, Ahmet; Balkanli, Didem (SPRINGER, 2026)
In this study, the pyrolytic behaviors of cotton stalk (CS), wool waste (WW), and their 1:1 blended mixture (CS-WW) were investigated using thermogravimetric analysis (TGA/DTG), isoconversional kinetic modeling, and thermodynamic analysis. The TGA results showed that CS underwent major mass loss (similar to 60%) primarily within the temperature range of 250-350 degrees C, whereas WW exhibited a broader degradation interval between 200 and 400 degrees C. The CS-WW blend displayed degradation characteristics reflecting contributions from both feedstocks, while the DTG curves exhibited multiple peaks associated with the overlapping multi-step degradation of lignocellulosic and proteinaceous components. Comparison of the theoretical and experimental TG/DTG profiles indicated that the thermal decomposition behavior of the blend was predominantly additive under the investigated conditions. The conversion-dependent activation energies determined using the Kissinger-Akahira-Sunose, Flynn-Wall-Ozawa, Starink, and Friedman methods varied over a wide range (approximately 61-223 kJ mol(-1)) depending on the degree of conversion and material type. Thermodynamic parameters (Delta H, Delta G, and Delta S) indicated that the pyrolysis processes were endothermic in nature. In addition, computational fluid dynamics (CFD) was employed as a supporting tool to evaluate the thermal and flow conditions within the reactor and to support the interpretation of the experimentally obtained thermal degradation behavior. Overall, the findings provide a comparative kinetic and thermodynamic assessment of single and blended biomass wastes, contributing to the understanding of their thermal conversion behavior for bioenergy and carbon-based material applications.
Keywords: Biochar; Model-free methods; Pyrolysis; Thermogravimetric analysis; Waste biomass; THERMAL-DEGRADATION; PROXIMATE ANALYSIS; BIOMASS; WOOD; DERIVATION; ENERGY; CARBON; FTIR; CFD; Thermodynamics; Chemistry